Hypothesis of Piezoelectricity of Inner Core As the Origin of Geomagnetism - Y Hayakawa (Data Science Journal, 2009)
A novel hypothesis is proposed that assumes piezoelectricity of the inner core as the origin of geomagnetism. By high pressure, electric charge is created on the surface and at the center of the earth. Inner core rotation yields a magnetic field. From the intensity and direction of geomagnetism at the present time, the surface charge density of the inner core is assumed to be -2x10-5C/m2. The rotation axis of the inner core is inclined by 10.4 degrees from that of the mantle. The inner core rotates with the mantle rotation. The reason for this is thought to be the eddy currents induced in the outer core of electrically conductive fluid that rotates with the mantle.